Application of Video Mapping Technique in Kotak Band Video Music - Inovensius Hugo Bima Wicaksana (Bina Nusantara University, 2022)
In the current development of visual videography technology, especially in the creation of music video content, new media are developing very rapidly, one of which is video projection (Projection Mapping). apart from the screen. Video Mapping is one of the newest video projection techniques used to convert almost any surface into a dynamic video display. The purpose of video mapping is to create the physical illusion of an image by combining visual elements. Most of the mapping projects are used in fashion shows, corporate events, concerts, and theater performances and can be an asset in artistic music videos. This research explains how to implement video projection into an artistic asset. Then displayed in public spaces to reach a wider audience. This paper will focus on the aspect of video mapping with the technical aspects of developing the concept of the Musik Video Kotak Band project entitled Wings of Garuda by using visual elements of applying visual video mapping in music videos to convey visual messages in video projections on the faces of the band members of the Kotak band. visual delivery in projection mapping creates artistic innovation in music video visuals to minimize the number of production teams in music video projects and messages in video projection visuals can convey their messages, the visuals will be perfected in the editing process to achieve the desired contrast so that video projections on the face more visible detail.